2011
DOI: 10.1111/j.1365-2486.2011.02570.x
|View full text |Cite
|
Sign up to set email alerts
|

Arctic warming on two continents has consistent negative effects on lichen diversity and mixed effects on bryophyte diversity

Abstract: Little is known about the impact of changing temperature regimes on composition and diversity of cryptogam communities in the Arctic and Subarctic, despite the well-known importance of lichens and bryophytes to the functioning and climate feedbacks of northern ecosystems. We investigated changes in diversity and abundance of lichens and bryophytes within long-term (9-16 years) warming experiments and along natural climatic gradients, ranging from Swedish subarctic birch forest and subarctic/subalpine tundra to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
120
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(150 citation statements)
references
References 61 publications
26
120
0
Order By: Relevance
“…Sphagnum increased at 11 of the 12 plots where it had more than 1% cover. This is consistent with Lang et al (2012), who found that while most bryophytes declined with experimental or naturally warmer temperatures, Sphagnum and common pleurocarpous mosses responded positively.…”
Section: Bryophytessupporting
confidence: 91%
“…Sphagnum increased at 11 of the 12 plots where it had more than 1% cover. This is consistent with Lang et al (2012), who found that while most bryophytes declined with experimental or naturally warmer temperatures, Sphagnum and common pleurocarpous mosses responded positively.…”
Section: Bryophytessupporting
confidence: 91%
“…An interesting exception is that BSCs dominated by mosses were relatively unaffected by experimental warming [39], suggesting a lower sensitivity than lichens or cyanobacteria to increases in temperature. Warming-induced decreases in lichen abundance are not restricted to drylands, as similar results have also been detected in arctic ecosystems [78]. However, the primary stress factor in these ecosystems is cold temperatures, rather than low water availability.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies found contrasting effects of climate change on bryophytes in tundra ecosystems (e.g. Klanderud and Totland 2005;Hassel et al 2012;Ja¨gerbrand et al 2012;Lang et al 2012). This was largely attributed to an inconsistent response of bryophytes to shading effects (Alatalo 1998;Marschall and Proctor 2004;Ja¨gerbrand and During 2005).…”
Section: Lichens and Bryophytesmentioning
confidence: 99%